2018
DOI: 10.31235/osf.io/r5tnq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Nationalist Backlash to International Refugee Law: Evidence from a Survey Experiment in Turkey

Abstract: How do international laws affect citizens’ willingness to accept refugees? In full and partial democracies, citizens’ attitudes can influence national policy on accepting refugees. A growing literature suggests international institutions can influence citizens’ attitudes on foreign policy issues, but those studies are almost entirely confined to domestic human rights and U.S.-based respondents; none consider refugee policy. Using data from a survey experiment administered in September 2017 via face-to-face int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…The intergroup effect remained significant even after employing an incentive to select the ruling best supported by the legal evidence. Likewise, Cope and Crabtree (2020) found that attitudes toward the implementation of international human rights were driven by the political‐party affiliation. Sulitzeanu‐Kenan et al (2016) show that ideological preferences strongly influence legal expert's judgments regarding the proportionality of hypothetical scenarios describing targeted killings of terrorists (Sulitzeanu‐Kenan et al, 2016).…”
Section: Theoretical Framework: Biases That Cause and That Might Solv...mentioning
confidence: 99%
“…The intergroup effect remained significant even after employing an incentive to select the ruling best supported by the legal evidence. Likewise, Cope and Crabtree (2020) found that attitudes toward the implementation of international human rights were driven by the political‐party affiliation. Sulitzeanu‐Kenan et al (2016) show that ideological preferences strongly influence legal expert's judgments regarding the proportionality of hypothetical scenarios describing targeted killings of terrorists (Sulitzeanu‐Kenan et al, 2016).…”
Section: Theoretical Framework: Biases That Cause and That Might Solv...mentioning
confidence: 99%
“…Türkiye'de yürütülen deneysel göç çalışmalarına bakıldığında ise, Türkiye sahasında göç konusunu deneysel yöntemler aracılığıyla araştıran çalışmaların özellikle 2015 yılı sonrasında arttığı görülmektedir. Bu çalışmalar yerli halkın göç politikası tercihleri (Cope ve Crabtree, 2020;Vrânceanu vd., 2021), göç etme niyetleri (Gevrek vd., 2021) ve göçmenlere karşı tutumları (Getmansky vd., 2018(Getmansky vd., , 2020Lazarev ve Sharma, 2017) gibi konuların yanı sıra mültecilerin geri dönme kararları (Husein ve Wagner, 2020) ve barış süreçlerine ilişkin tercihleri (Fabbe vd., 2017) gibi konulara odaklanmaktadır. Ancak Türkiye'de yürütülen deneysel göç çalışmalarının yalnızca küçük bir kısmının Türkiye'deki üniversitelerde ve devlet kurumlarında görev yapan araştırmacılar tarafından yürütüldüğü de dikkat çekmektedir.…”
Section: Journal Of Ethnic and Migrationunclassified